Psychogenic alopecia in a cat treated by Neural Therapy: case report - Lima Gonçalves, Bruna (Pubvet, 2020)
Neural Terapy (NT) is a form of treatment that consists in the use of local anesthetics in low concentrations in diverse body areas of the patien, chosen by his life history. The scientific bases have begun with the russians Pavlov and Speransky, later with the german brothers Huneke, Pischinger and Hans H. Reckeweg have importance too, among others. It is practiced in Austria, Germany, Argentina, Brazil, Canada, Chile, Colombia, Costa Rica, Cuba, Spain, United States, Mexico, Switzerland, Turkey and some other countries. It consists in a regulatory therapy that seeks to activate the organism self-regulating mechanisms. The objective of this work was to demonstrate the effectiveness of Neural Therapy in an animal with psychogenic alopecia.